2005
DOI: 10.1093/toxsci/kfi249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Estrogenic Activities of Aquatic Herbicides and Surfactants Using an Rainbow Trout Vitellogenin Assay

Abstract: Estrogenic potencies of four herbicides (triclopyr, 2,4-dichlorophenoxyacetic acid (2,4-D), diquat dibromide, glyphosate), two alkylphenol ethoxylate-containing surfactants (R-11 and Target Prospreader Activator (TPA)), and the binary mixture of surfactants with the herbicides were evaluated using an in vivo rainbow trout vitellogenin assay. Juvenile rainbow trout exposed to 2,4-D (1.64 mg/l) for 7 days had a 93-fold increase in plasma vitellogenin (Vtg) levels compared with untreated fish, while rainbow trout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
47
2
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 38 publications
4
47
2
3
Order By: Relevance
“…At concentrations above the LOECs, however, the binary mixture response was less than the simple addition of each individual component's response and at the highest concentration tested the binary mixture response was eliminated completely, suggesting that the effects of estrogenic mixtures are dose-dependent. The nonmonotonic (inverted-U shaped) dose-response relationships observed for 4,4 0 DDE, trans-nonachlor and their combination in the present study are not uncommon; similar dose-response relationships have been observed for other estrogenic compounds tested in in vitro and in vivo models [38][39][40]. The specific mechanisms mediating the reduction in cell proliferation at high concentrations observed in the present study are unknown, but could include cytotoxicity [39], and inhibition of growth due to the downregulation of E 2 receptors [41].…”
Section: Discussionsupporting
confidence: 84%
“…At concentrations above the LOECs, however, the binary mixture response was less than the simple addition of each individual component's response and at the highest concentration tested the binary mixture response was eliminated completely, suggesting that the effects of estrogenic mixtures are dose-dependent. The nonmonotonic (inverted-U shaped) dose-response relationships observed for 4,4 0 DDE, trans-nonachlor and their combination in the present study are not uncommon; similar dose-response relationships have been observed for other estrogenic compounds tested in in vitro and in vivo models [38][39][40]. The specific mechanisms mediating the reduction in cell proliferation at high concentrations observed in the present study are unknown, but could include cytotoxicity [39], and inhibition of growth due to the downregulation of E 2 receptors [41].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, there were no treatment-related histopathologic changes in fish testes or ovaries in any 2,4-D-exposed group. In contrast, induction of plasma VTG was observed in juvenile RT treated with 2,4-D, and the response was enhanced by coexposure to a commercial surfactant mixture (Xie et al 2005).…”
Section: Discussionmentioning
confidence: 83%
“…These data are compared with those from an earlier RT study that measured plasma VTG protein after treatment with 2,4-D (Xie et al 2005). One potential reason for the discrepancy may be the innate variability of VTG mRNA in liver compared with plasma VTG protein measurements in RT plasma.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Paul et al (2006) reported the effects of 2,4-D on several aquatic species: Brook trout (Salvelinus fontinalis), walleye (Sander vitreus), fathead minnow (Pimephales promelas), and the amphipod (Hyallela azteca) in static acute toxicity tests in the laboratory. Estrogenic activities of aquatic herbicides using rainbow trout were evaluated by Xie et al (2005). The other estrogenic compound, bisphenol A, may lead to problems in either mating or sexual behavior due to the difference in growth and disparity of sexual maturation between male and female fish (Na et al 2002).…”
Section: Discussionmentioning
confidence: 99%